At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Experience the ease of finding accurate answers to your questions from a knowledgeable community of professionals. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To solve the problem, we need to find the derivative of the function:
[tex]\[ f(x) = \frac{4x^{10} - 10x^6 - 4}{2x^2} \][/tex]
Let's follow through the steps to simplify the function and then find its derivative.
### Step 1: Simplify the Function
First, we simplify the given function:
[tex]\[ f(x) = \frac{4x^{10} - 10x^6 - 4}{2x^2} \][/tex]
We can distribute the denominator [tex]\( 2x^2 \)[/tex] across each term in the numerator:
[tex]\[ f(x) = \frac{4x^{10}}{2x^2} - \frac{10x^6}{2x^2} - \frac{4}{2x^2} \][/tex]
Now simplify each fraction:
[tex]\[ f(x) = \frac{4x^{10}}{2x^2} = 2x^8 \][/tex]
[tex]\[ f(x) = \frac{10x^6}{2x^2} = 5x^4 \][/tex]
[tex]\[ f(x) = -\frac{4}{2x^2} = -\frac{2}{x^2} = -2x^{-2} \][/tex]
Putting it all together, we have:
[tex]\[ f(x) = 2x^8 - 5x^4 - 2x^{-2} \][/tex]
### Step 2: Find the Derivative
To find the derivative [tex]\( f'(x) \)[/tex], we need to differentiate each term:
[tex]\[ f(x) = 2x^8 - 5x^4 - 2x^{-2} \][/tex]
Let's find the derivatives term by term:
1. For [tex]\( 2x^8 \)[/tex]:
[tex]\[ \frac{d}{dx}[2x^8] = 16x^7 \][/tex]
2. For [tex]\( -5x^4 \)[/tex]:
[tex]\[ \frac{d}{dx}[-5x^4] = -20x^3 \][/tex]
3. For [tex]\( -2x^{-2} \)[/tex]:
[tex]\[ \frac{d}{dx}[-2x^{-2}] = 4x^{-3} \][/tex]
Combining all these results, the derivative of [tex]\( f(x) \)[/tex] is:
[tex]\[ f'(x) = 16x^7 - 20x^3 + 4x^{-3} \][/tex]
Therefore, the derivative [tex]\( f'(x) \)[/tex] of the given function is:
[tex]\[ f'(x) = \boxed{(20x^{9} - 30x^{5})/x^2 - 2(2x^{10} - 5x^{6} - 2)/x^3} \][/tex]
[tex]\[ f(x) = \frac{4x^{10} - 10x^6 - 4}{2x^2} \][/tex]
Let's follow through the steps to simplify the function and then find its derivative.
### Step 1: Simplify the Function
First, we simplify the given function:
[tex]\[ f(x) = \frac{4x^{10} - 10x^6 - 4}{2x^2} \][/tex]
We can distribute the denominator [tex]\( 2x^2 \)[/tex] across each term in the numerator:
[tex]\[ f(x) = \frac{4x^{10}}{2x^2} - \frac{10x^6}{2x^2} - \frac{4}{2x^2} \][/tex]
Now simplify each fraction:
[tex]\[ f(x) = \frac{4x^{10}}{2x^2} = 2x^8 \][/tex]
[tex]\[ f(x) = \frac{10x^6}{2x^2} = 5x^4 \][/tex]
[tex]\[ f(x) = -\frac{4}{2x^2} = -\frac{2}{x^2} = -2x^{-2} \][/tex]
Putting it all together, we have:
[tex]\[ f(x) = 2x^8 - 5x^4 - 2x^{-2} \][/tex]
### Step 2: Find the Derivative
To find the derivative [tex]\( f'(x) \)[/tex], we need to differentiate each term:
[tex]\[ f(x) = 2x^8 - 5x^4 - 2x^{-2} \][/tex]
Let's find the derivatives term by term:
1. For [tex]\( 2x^8 \)[/tex]:
[tex]\[ \frac{d}{dx}[2x^8] = 16x^7 \][/tex]
2. For [tex]\( -5x^4 \)[/tex]:
[tex]\[ \frac{d}{dx}[-5x^4] = -20x^3 \][/tex]
3. For [tex]\( -2x^{-2} \)[/tex]:
[tex]\[ \frac{d}{dx}[-2x^{-2}] = 4x^{-3} \][/tex]
Combining all these results, the derivative of [tex]\( f(x) \)[/tex] is:
[tex]\[ f'(x) = 16x^7 - 20x^3 + 4x^{-3} \][/tex]
Therefore, the derivative [tex]\( f'(x) \)[/tex] of the given function is:
[tex]\[ f'(x) = \boxed{(20x^{9} - 30x^{5})/x^2 - 2(2x^{10} - 5x^{6} - 2)/x^3} \][/tex]
Thanks for using our service. We aim to provide the most accurate answers for all your queries. Visit us again for more insights. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.